Likelihood of obstructive sleep apnea in people living with HIV in Cameroon – preliminary findings. Issue 1 (December 2017) - Njoh, Andreas; Mbong, Eta; Mbi, Valeri; Mengnjo, Michel; Nfor, Leonard; Ngarka, Leonard; Chokote, Samuel; Fonsah, Julius; Kingue, Samuel; Ntone, Felicien; Njamnshi, Alfred
Abstract Background Obstructive Sleep Apnea (OSA) has been observed to be common among people living with HIV/AIDS (PLWHA). Sleep scales can be used to screen patients at increased "risk" of OSA who can benefit from polysomnography. This study therefore sought to generate preliminary data on this often unattended complication of HIV Infection in Cameroon. Methods A case control study carried out at the Yaoundé Central Hospital in which 82 participants were enrolled: 39 PLWHA age- and sex-matched with 43 controls. The Berlin sleep questionnaire was used to assess the likelihood of OSA in both groups. Results Participants were aged 20 to 59 years with a mean age of 34.27 ± 9.29 (35.72 ± 10.09 and 32.92 ± 8.41 respectively for cases and controls, p  = 0.180). Cases (PLWHA) compared to controls had higher likelihood of OSA (43.6% versus 14.0%, AOR 3.93 95% CI 1.12–13.80 on adjusting for socioeconomic status, depression and smoking) as well as 10 times higher rates of daytime somnolence (23.1% versus 2.3%, p  = 0.005). Significant differences were found between PLHWA at "risk" of OSA and those without only with regards to rate of compliance to Highly Active anti-Retroviral Therapy (HAART), and mean abdominal and waist circumferences. Conclusions The likelihood of obstructive sleep apnea (OSA) in PLHWA is higher than in HIV negative controls. Integration of screening for OSA in HIV/AIDS care with the aid of sleep scales would permit timely diagnosis and management and reduce the incidence of chronic cardiorespiratory co-morbidities in PLWHA.